2022
DOI: 10.1097/pec.0000000000002760
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Usage of Safety Equipment Provided Through a Community Partnership Approach to Injury Prevention in the Pediatric Emergency Department

Abstract: Objectives: Previous studies have shown that educational programs in conjunction with provision of free or low-cost safety equipment increases the likelihood of parents changing behaviors at home. This project surveyed caregivers in the pediatric emergency department (ED) about safety behaviors before and after provision of education and safety equipment related to medication storage, firearm storage, and drowning. Methods:A convenience sample of families presenting to the ED for any complaint with a child of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Previous work has shown that patient adherence is improved when education is paired with safety equipment that families can use (Kendrick et al 2009 , 2012 ). A prior study at our PED in 2019 partnered with the School of Public Health (SPH) and surveyed caregiver practices regarding medication storage, firearm storage, and other safety practices while also providing safety equipment to participants (Webb et al 2022 ). This study demonstrated that caregivers often report unsafe storage of medications and firearms and showed effective outreach by partnering with local schools and resources.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that patient adherence is improved when education is paired with safety equipment that families can use (Kendrick et al 2009 , 2012 ). A prior study at our PED in 2019 partnered with the School of Public Health (SPH) and surveyed caregiver practices regarding medication storage, firearm storage, and other safety practices while also providing safety equipment to participants (Webb et al 2022 ). This study demonstrated that caregivers often report unsafe storage of medications and firearms and showed effective outreach by partnering with local schools and resources.…”
Section: Introductionmentioning
confidence: 99%